The live experience of people suffered by leprosy - Mukhlasin Mukhlasin; Tukimin Sansuwito; Asita Elengoe; Andiko Nugraha Kusuma (Intelektual Pustaka Media Utama, 2023)
Leprosy, unlike other high-fatality diseases, is a long-term, chronic illness that can cause long-term disability. People's experiences with leprosy in Indonesia, indicating a need for responsive leprosy services to meet the wide range of requirements, including care for those who are not formally afflicted with the disease. This study aimed to explore live experience of people affected by leprosy in the community in Banten province, Indonesia. This study employed inductive phenomenological research methods with a semi-structure interview. We used snowball sampling, and people who could not communicate or did not want to take part in the study were not included. The majority of the participants were below 45 years, and 21 were male and 19 were female. Among total participants, only 15% could not read and write. The data were examined using Colaizzi's phenomenological analysis, which involves collecting and analysing data in parallel until no new information is acquired. We established trustworthiness in qualitative studies. The following themes emerged from this study: i) public understanding about leprosy; ii) psychological response; iii) perceived stigma; iv) health seeking behavior; and v) leprosy's impact on economic condition. This study identified the meaning of leprosy patients' lives through their own voices. People who have leprosy should also get spiritual help, coping skills, and training in self-care skills.